Early Entecavir Treatment for Chronic Hepatitis B with Severe Acute Exacerbation - Tsai, Wei-Lun (American Society for Microbiology, 2014)
A previous study found that lamivudine, if started early enough, may improve the chance of survival in chronic hepatitis B virus (HBV) with severe acute exacerbation (SAE). The aim of this study was to investigate the effect of early entecavir treatment before the bilirubin level exceeds 20 mg/dl for chronic HBV with SAE. Consecutive patients with chronic HBV with SAE and a serum bilirubin level of <20 mg/dl who received lamivudine or entecavir were enrolled. Short-term (4 months) survival was evaluated. One hundred fourteen patients received lamivudine, and 53 patients received entecavir. The baseline characteristics were similar for the two groups except that the entecavir group was older and had a lower alanine aminotransferase (ALT) level. Three patients (8.0%) in the entecavir group and 9 patients (7.9%) in the lamivudine group died (P = 1.000). If only patients who started antiviral treatment before serum bilirubin level rose to more than 15 mg/dl were included, 3 patients (8.3%) in the entecavir group and 3 patients (3.0%) in the lamivudine group died (P = 0.189). If only patients with an HBV DNA level higher than 10(5) copies/ml and a bilirubin level lower than 15 mg/dl were included, 5 out of 40 patients (12.5%) in the entecavir group died and 1 out of 59 patients (1.7%) in the lamivudine group died. Multivariate analysis found that entecavir treatment was associated with more mortality than lamivudine (P = 0.035). Early entecavir treatment in patients with high viral load is associated with more short-term mortality than lamivudine for chronic HBV with severe acute exacerbation.